Transfers, information and management advice: Direct effects and complementarities in Malawi - Ambler, Kate; de Brauw, Alan; Godlonton, Susan (Elsevier, 2026)
We examine a program designed to alleviate credit, information, and farm management constraints among smallholder cash crop farmers through transfers and a cross-randomized program offering intensive agricultural extension. We document strong complementarities between the two sets of interventions. Investment driven by increased labor expenditures, production, and consumption are highest for farmers that received both transfers and intensive extension, a pattern that persists two and three years later. In the short run, transfers alone led to the reallocation of input expenditures into increased labor for cash crop cultivation, which led to increased production of project focal crops but not total crop production. While farmers in the transfers only group continue to spend more on labor in subsequent seasons, this does not lead to changes in production or consumption, suggesting that the support of the intensive extension was important for the generation of the largest welfare gains from the transfers.